Survei Cross-Sectional Online Untuk Menilai Vaksin Covid-19 Terkait Akseptabilitas, Pengetahuan dan Kesediaan Membayar di Kalangan Mahasiswa Kesehatan Masyarakat di Provinsi Sumatera Utara - Daniel Ginting; Nina Fentiana; Rahmat Alyakin Dachi (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of the study was to assess the Covid-19 vaccine related to acceptability, knowledge and willingness to pay among public health students in North Sumatra Province. The research design is an online cross-sectional survey using "Google Form" with a sample of all public health students at Sari Mutiara Indonesia University and Prima Indonesia University who have not received the Covid-19 vaccine (91 respondents). The study found that the acceptability of the Covid-19 vaccine among public health students in North Sumatra Province was still low (46.2%) as was the willingness to pay (36.3%). There is no relationship between knowledge and acceptability of the Covid-19 vaccine. The majority of public health students think vaccines are a cure for COVID-19. There is a significant relationship between willingness to pay and the acceptability of the Covid-19 vaccine for public health students, so the free vaccine program will determine the level of coverage of the Covid-19 vaccination. Health education campaign interventions about the Covid-19 vaccine from public health experts are needed to straighten students' knowledge of the Covid-19 vaccine, which is ultimately expected to be able to build confidence in the effectiveness of the Covid-19 vaccine.